IbKIK Jasa Konsultansi Talent Management - Yanuar Fauzuddin (Asian Journal of Innovation and Entrepreneurship, 2017)
AbstractThe business unit developed called IbKIK Talent Management Consultancy Services (IbKIK JKTM) with main activities as a provider of research and development services in business and economics. Short-term goal is to meet and support the needs of the community, partners and businesses of of consultancy and training services in business and economics field. While the long-term goal IbKIK JKTM is the creation of a system of good governance, among others: a data base of research results and superior technology, a data base of client needs, index of client satisfaction, guidelines for unit activities of IbKIK, the working mechanism of IbKIK, creation of favorable cooperation between the UWP Surabaya with industry, local government and the community, an increasing number of new entrepreneurs of lecturers and students. The method applied is to maintain the existing condition of raw materials or clients and maintaining good relationships with customers or clients, especially clients remain. The production had a very adequate instrument assets, production process starting from understanding the client's needs until the implementation of the consultation as well as feedback and supervision to maintain good relationships with clients. The management is still not good so it need improvement, the marketing is done by segmenting and targeting strategy, pricing, promotion and maintaining good relationships with clients (developing relationship). While human resources are adequate to the needs of training and development, the existing facilities dedicated space business unit, but the ingredients are still to be developed. From the financial side, the financial return in 2016 are projected to reach Rp. 500.000.000, -. Accountability income and expenditure of money is managed independently by the management. The next steps to operate the business are improving organizational management especially in financial management, improving marketing strategy, developing products, increasing human resource competencies, maintaining existing clients and increasing public training.